Growth Factors and Anticatabolic Substances for Prevention and Management of Intervertebral Disc Degeneration - Umile Giuseppe Longo; Stefano Petrillo; Edoardo Franceschetti; Nicola Maffulli; Vincenzo Denaro (Hindawi Limited, 2012)
Intervertebral disc (IVD) degeneration is frequent, appearing from the second decade of life and progressing with age. Conservative management often fails, and patients with IVD degeneration may need surgical intervention. Several treatment strategies have been proposed, although only surgical discectomy and arthrodesis have been proved to be predictably effective. Biological strategies aim to prevent and manage IVD degeneration, improving the function and anabolic and reparative capabilities of the nucleus pulposus and annulus fibrosus cells and inhibiting matrix degradation. At present, clinical applications are still in their infancy. Further studies are required to clarify the role of growth factors and anticatabolic substances for prevention and management of intervertebral disc degeneration.